Optimization of Slaughter Age of Jamuna Basin Lamb Based on Carcass Traits and Meat Quality - Hossain, MA; Rahman, MM; Rahman, MW; Hossain, MM; Hashem, MA (SAARC Journal of Agriculture, 2022)
The aim of this study was to identify optimum slaughter age on carcass traits and meat quality of Jamuna basin lambs. Thirty lambs were divided into three age groups like T1 (6 months), T2 (9 months) and T3 (12 months) having ten lambs of each treatment. Parameters studied were carcass traits, proximate component (DM, CP, EE, and Ash), physicochemical (Ultimate pH, cooked pH, cooking loss, drip loss, water holding capacity-WHC), sensory attributes (color, flavor, tenderness, juiciness, overall acceptability) and instrumental color values (L*, a* and b*). Hot carcass weight and dressing% were found significantly (p<0.001) higher in T3 than T1 and T2 treatments. Edible by products namely viscera, head, leg, pluck, neck, shoulder, rack, loin, kidney, heart, liver, lungs and shank from three treatments were found significant effect (p<0.001). Inedible by products viz. blood, skin and spleen were found significantly higher (p<0.001) with the advancement of age. Dry matter (DM) of T2 and T3 were found significantly lower (p<0.001) than T1 treatment. Crude protein (CP) and ether extract (EE) were significantly increased (p<0.001) of advancement of age of lambs. Drip loss of T2 was found significantly lower and WHC of T2 was significantly (p<0.001) higher than other two treatments. Cooking loss and ultimate pH of T3 were significantly (p<0.001) lower than other two treatments. Color, tenderness, juiciness and overall acceptability were significantly differed (p<0.001) and flavor was significantly differed (p<0.001). The instrumental color values L* decreased whereas a* and b* and chroma values were significantly (p<0.05) increased with the advancement of age of lambs. The saturation index was significantly (p<0.001) higher in 6- and 12-months age than 9 months of age. It is revealed from the study that 12 months of slaughter age showed better in terms of productive and meat quality traits. Therefore, 12 months of age may be recommended as optimum slaughter age for Jamuna basin lambs. SAARC J. Agric., 19(2): 257-270 (2021)